الاتجاهات نحو العولمة لدى طلبة التربية البدنية والرياضية في بعض المعاهد الجزائرية "دراسة ميدانية على طلبة باتنة،وسوق أهراس" - محمد الشريف, ناصـري (دفـاتر المـــــــــــخبـر; No 14 (2015): مجلة دفاتر, 2018)
ملخص الدراسة: يهدف هذا البحث إلى دراسة مستوى تأثير العولمة على طلبة علوم الرياضةوفقا لمجموعة من المتغيراتوذلك بتطبيق استبيان للاتجاهات نحو العولمة من إعداد الباحث.و من أجل ذلك تم طرح مجموعة من التساؤلات والفرضيات، وتوصل الباحث إلى وجود اختلاف في مستوى تأثر الطلبة بالعولمة بمستويات مختلفة بين المتوسطة إلى المرتفعة،مع عدم وجود فروق بين الطلبة في مستوى تأثير العولمة ككل وأبعادها المختلفة يرجع إلى المستوى الدراسي،مع وجود فروق دالة في مستوى تأثير العولمة في المقياس ككل وبعض الأبعاد الفرعية وفق متغير مكان السكن Abstract: This research aims to study the impact of globalisation among the students of sports science, for it was introduced a set of questions and hypotheses. The researcher concluded that there is there is a difference in the level of affected students globalisation at different levels between the medium to high, with no differences between the students in the level of the impact of globalization as a whole and taken away different due to the level of study, with the presence of significant differences in the level of the impact of globalization in the measure as a whole and some sub-dimensional variable according to place of residence